An evaluation of a logbook for trainees in accident & emergency medicine in the United Kingdom: senior consultant opinion. Issue 1 (March 1993) - Luke, C; Kadzombe, E; Gorman, D; Armstrong, A
Abstract : A previous paper from the Merseyside Group of Senior Registrars in Accident & Emergency Medicine examined the desirability of a logbook for Higher Specialist Training (HST) in accident & emergency medicine in the United Kingdom and its principal ingredients (Luke et al., 1991). A survey of 100 senior registrars and recently appointed consultants in the specialty identified the main issues of importance to the majority of respondents e.g. certification in advanced cardiac and trauma life support, a minimum of three years in the specialty before appointment as senior registrar and certain key secondments. In this paper, more senior consultants in the specialty were surveyed and a resounding majority concurred with the preferences of their junior colleagues. The findings are discussed and the implications for a future curriculum for postgraduate training in A&E medicine are explored.